A novel extended state observer. (September 2015) - Xiong, Shaofeng; Wang, Weihong; Liu, Xiaodong; Chen, Zengqiang; Wang, Sen
Abstract: A novel extended state observer, which feeds back the output estimation error via both nonlinear and switching terms, is put forward for the first time in this paper. No longer neglecting the lumped uncertainty׳s first time derivative, the problem of disturbance observer design is transformed into the problem of state observer design in the presence of external disturbance. The switching term of the output estimation error is employed to counteract the adverse effect of external disturbance. The newly developed extended state observer provides an attractive solution to the issue of high precision motion control system. Both numerical simulation and experimentation on a speed turntable with temperature box are implemented to verify the performance of the proposed newly developed extended state observer. Highlights: Although the traditional ESO has achieved success in diverse fields, it fails to obtain satisfactory performance in some special case. A novel ESO, which feeds back the output estimation error via both nonlinear and switching terms, is proposed. The experimentation on a speed turntable with temperature box is implemented to verify the performance of the new ESO.